Internet world guide to webcasting - Miles, Peggy, 1959- 4 0 16; 5 (New York : Wiley, 1998)
Looks at how organizations around the world are using webcasting for a variety of purposes, and explains how to use Web technology to create a network as an Internet broadcaster.
Wiley Computer Publishing.
Includes bibliographical references (p. 385-386) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Webcasting.;Webcasting.; 20; 2